Kajian Kriminologis Terhadap Minuman Beralkohol (Sopi) Dengan Tindak Pidana Yang Terjadi Di Kabupaten Kepulauan Aru - Luturmas, Resi; Adam, Sherly; Leasa, Elias Zadrach (Bacarita Law Journal, 2023)
The crimes that arise in the Aru Islands district due to the consumption of alcoholic drinks (sopi) have been increasing lately, so efforts must be made to resolve them so that no more crimes occur. This study aims to examine and discuss what crimes are caused by consuming alcoholic beverages (sopi) in the Aru Islands district. The type of research used in this research is empirical-juridical or sociological-juridical. The data sources used are primary data and secondary data. Techniques for collecting legal materials through interviews, documentation studies, and qualitative analysis of legal materials. The results of the study show that the factors causing the occurrence of criminal acts caused by consuming alcoholic beverages (sopi) are many, including unemployment, excessive alcohol consumption, and the fact that most people still use alcoholic beverages (sopi) as an outlet. The efforts made by the Aru Islands Police include conducting campaigns among teenagers as well as carrying out operations and enforcing the law against perpetrators of the distribution of alcoholic beverages (sopi).